Ethics of Gender Roles in The Family: Qur’anic Perspective - Marwati, Andi; Hamka Hasan; Nur Arfiyah Fabriyani (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2025)
This study aims to examine the ethics of gender roles in the household from the perspective of the Qur'an, focusing on reconstructing the roles of men and women in addressing the problems of gender injustice and the phenomenon of fatherlessness. This research employs a literature study method by analyzing relevant Qur'anic verses, contextualized with classical and contemporary tafsir, as well as the thoughts of scholars such as Al-Zamakhshari, At-Tabari, Muhammad Abduh, Amina Wadud, Asma Barlas, and Ziba Mir-Hosseini. The findings show that the Qur'an affirms the spiritual and moral equality of men and women, and emphasizes the principle of partnership through the concepts of zawj (complementarity) and qiwāmah (functional responsibility). The ethics of gender roles in the household are built upon the principles of ‘adl (justice), ihsan (benevolence), flexibility in role distribution, and maslahah (public interest), so that the husband-wife relationship is not hierarchical but complementary according to conditions and social contexts. Thus, the purpose of this paper is to affirm that the Qur'an provides a dynamic ethical framework to realize justice and family harmony, while also opening space for ijtihad in responding to contemporary challenges.